2006
DOI: 10.1096/fj.05-4890fje
|View full text |Cite
|
Sign up to set email alerts
|

Transmissibility of mouse AApoAII amyloid fibrils: inactivation by physical and chemical methods

Abstract: AApoAII amyloid fibrils have exhibited prion-like transmissibility in mouse senile amyloidosis. We have demonstrated that AApoAII is extremely active and can induce amyloidosis following doses less than 1 pg. We tested physical and chemical methods to disrupt AApoAII fibrils in vitro as determined by thioflavin T binding and electron microscopy (EM) as well as inactivating the transmissibility of AApoAII fibrils in vivo. Complete disruption of AApoAII fibrils was achieved by treatment with formic acid, 6 M gua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…A few recent studies have shown that AA-containing extracts also had amyloid-inducing activity when administered orally to mice (36,37). In AApoAII amyloidosis, we reported that an oral administration of AApoAII amyloid fibrils induced amyloidosis in recipient mice (38). Thus, it is plausible that oral ingestion of AA-containing fecal matter caused amyloid deposition in the cheetah population.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A few recent studies have shown that AA-containing extracts also had amyloid-inducing activity when administered orally to mice (36,37). In AApoAII amyloidosis, we reported that an oral administration of AApoAII amyloid fibrils induced amyloidosis in recipient mice (38). Thus, it is plausible that oral ingestion of AA-containing fecal matter caused amyloid deposition in the cheetah population.…”
Section: Discussionmentioning
confidence: 70%
“…The lyophilized fibrils were dissolved in DW (1.0 mg/ml) and used immediately for injection (42). The other lyophilized AA fibrils were treated with 88% formic acid for 8 h at room temperature followed by dialysis against DW for 6 h before injection (38).…”
Section: Isolation Of Amyloid Fibrils and Western Blot Analysismentioning
confidence: 99%
“…Thus the period for detection decreased to less than 1 month compared to Tg À/À mice. 54 Since fibrilization of several kinds of amyloid proteins is nucleation-dependent, self-and cross-seeding by amyloid fibrils and amyloid fibril-like materials is thought to be a key factor for the progress of amyloidosis. To elucidate the pathogenesis of amyloidosis and to prevent it, it is necessary to improve the current bio-assay system for detection of amyloid fibrils and amyloidogenic materials in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration was slowed by 6 M urea or by autoclaving, and it was not changed by formalin, DNAse or RNAse treatments. This finding revealed that transmissibility of AApoAII depends on fibril conformation (H. Zhang et al, 2006). .P1-Apoa2 c mice that were kept in the same cage with mice having amyloidosis for 3 months developed amyloidosis.…”
Section: Transmission Of Mouse Aapoaii Amyloidosismentioning
confidence: 91%